TINJAUAN RETROSPEKTIF PENGARUH PEMBERIAN HALOPERIDOL TERHADAP GEJALA EKSTRAPIRAMIDAL PADA PASIEN SKIZOFRENIA DAN MENJALANI RAWAT INAP DI SALAH SATU RUMAH SAKIT DI BANDUNG - Cindy Lestari, Restia
Haloperidol is an essential drug in the treatment of schizophrenia. Extrapyramidal symptom (EPS) is one of the major adverse effects of haloperidol that needs particular consideration. This study was aimed to describe the profile of the incidence of EPS, and to find out factors that influence the incidence of EPS among the users of haloperidol. Research was done retrospectively on cross-sectional data of schizophrenic inpatients at one hospital in Bandung. The research was conducted using data on the patients’medical records, with a random sampling from a pre-determined population. The medical record was taken to represent the patient group based on the criterion, which was haloperidol user. The data taken were medical records of schizophrenic inpatients treated between January 1 st and December 31 st of 2012, in which there were 73 patients given haloperidol. There were three factors observed, mainly gender, age, and length of stay (LOS). Studied patients were 52 male (71.23%) and 21 female (28.77%). Based on age, the patients were grouped into ?40 years old (57 patients, 78.08%) and >40 years ole (16 patients, 21.92 %). Based LOS, the patients were classified as those who stay ?2 weeks (27 patients, 36.99%) and >2 weeks (46 patients, 63.01%). Statistical analysis showed that LOS significantly correlated with EPS (P<0.005). Altogether, results of the present study confirm that there is significant correlation between haloperidol usage and EPS. Furthermore, the results suggest that LOS determines the presence of EPS in schizophrenic patients.